Compositionally Designed 2D Ruddlesden–Popper Perovskites for Efficient and Stable Solar Cells. Issue 4 (6th April 2021) - Wei, Yi; Chen, Baoquan; Zhang, Fan; Tian, Yuyang; Yang, Xichuan; Cai, Bin; Zhao, Jijun
Abstract : Polymer Solar Cells In article number 2000661, Jijun Zhao and co‐workers authors designed 2D Ruddlesden‐Popper Perovskites to simultaneously enhance the stability and efficiency. The (FPEA)2 (FA)8 Pb9 I28 film is exceptionally vertically orientated and exhibits an extended absorption edge. A high‐performance solar cell with 16.15% efficiency is achieved. Its unencapsulated device maintains 95% of its stating PCE after 2112 h (30–70% RH).